Intra- and Inter-population Variability in Mamelon Expression on Incisor Teeth - Sassan Chegini-Farahini; Janet Fuss; Grant Townsend (Dental Anthropology Association, 2000)
Although rounded protuberances referred to as mamelons are observes commonly on the crowns of newly-emerged human incisor teeth, there have been very few systematic studies of their expression. The main aims of this study were to describe the nature and extent of variation of mamelon expression on permanent incisors within and between two different human populations, and to quantify the contributions of genetic and environmental influences to observed variability. Mamelon expression was scored according to a 12-grade system described by Fitzgerald et al (1983) using dental models of 104 indigenous Australians, as well as 287 singletons and 175 pairs of twins of European descent. Over 90% of all incisors displayed mamelons, although the pattern of expression differed significantly between maxillary and mandibular arches, tooth types and ethnic groups. There were no significant differences in expression between sexes of antimeric teeth. A three-mamelon form was most common on maxillary and mandibular central incisors in both ethnic groups, but different expressions were observed on lateral incisors. Percentage concordances for monozygotic twin pairs were higher generally than those for dizygotic twin pairs, indicating that genetic factors play a role in determining the mamelon expression.